2008
DOI: 10.1111/j.1600-079x.2007.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces body weight in goldfish (Carassius auratus): effects on metabolic resources and some feeding regulators

Abstract: The objective of the present study was to analyze the effects of chronic melatonin (10 microg/g body weight) on body weight and the main energetic reserves, particularly hepatic and muscle content of proteins, lipids and glycogen in goldfish. In addition, we studied plasma leptin and ghrelin, and hypothalamic content of neuropeptide Y (NPY) and monoamines after chronic melatonin treatment in order to elucidate a possible interplay between melatonin and these feeding regulators on the body weight regulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…mediated by IGF-I, 18,19 and Falcó n et al 20 demonstrated a direct role of melatonin on GH secretion. In addition, recent studies have shown that melatonin influences carbohydrates and lipid metabolism in goldfish liver and muscle 17 ; inconsistent results, instead, were found in mammals. [21][22][23] In this regard, among signals that regulate feeding behavior and metabolism, leptin (LPT) plays a key role as a satiety molecule controlling body weight maintenance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…mediated by IGF-I, 18,19 and Falcó n et al 20 demonstrated a direct role of melatonin on GH secretion. In addition, recent studies have shown that melatonin influences carbohydrates and lipid metabolism in goldfish liver and muscle 17 ; inconsistent results, instead, were found in mammals. [21][22][23] In this regard, among signals that regulate feeding behavior and metabolism, leptin (LPT) plays a key role as a satiety molecule controlling body weight maintenance.…”
Section: Introductionmentioning
confidence: 96%
“…7,14 In fish, a contrasting action of melatonin on growth has been observed: a significant weight increase was found in Atlantic salmon implanted with melatonin, 15 while in both trout and goldfish, implants or injections reduced body weight and growth rate. 16,17 On the other hand, it is well known that a central component of growth processes is the growth hormone (GH)-insulin-like growth factor-I (IGF-I) axis. Many of the growth-promoting actions of GH in fish are 1 Dipartimento di Scienze della vita e dell'ambiente, Università Politecnica delle Marche, Ancona, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine (DA) and serotonin (5-HT) systems have been found to inhibit food intake, while noradrenaline (NA) stimulates it (de Pedro et al, 1998a;de Pedro et al, 1998b). Moreover, interactions between monoaminergic systems and other feeding regulators have been previously reported in goldfish (de Pedro et al, 1998a;de Pedro et al, 2006;de Pedro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The content of NA, DA, DOPAC (a major DA metabolite), 5-HT and 5-HIAA (a major 5-HT metabolite) in hypothalamus and telencephalon were quantified by HPLC (Agilent 1100, Madrid, Spain) with coulometric detection (ESA Coulochem II, Chelmsford, MA, USA) as previously described (de Pedro et al, 2008). Briefly, the tissues were sonicated in 100 μl of cold perchloric acid (0.3 mol l −1 ; Scharlab, Sentmenat, Spain) containing 0.4 mmol l −1 sodium bisulphate and 0.4 mmol l −1 EDTA disodium salt dihydrate (Sigma Chemical).…”
Section: Oea Administrationmentioning
confidence: 99%
“…The plasma melatonin level in Mozambique tilapia Oreochromis mossambicus increases during the night and decreases at day (Nikaido et al 2009). Although it has been suggested that melatonin secretions affect physiological functions, including body growth in fish (Taylor et al 2005;Herrero et al 2007;De Pedro et al 2008;Maitra et al 2013), the effect of melatonin on the transcription of growth-related genes (ghrh and ss) is still unclear.…”
Section: Introductionmentioning
confidence: 99%